Genotypic and phenotypic resistance profiles of HIV-1 infected patients failing salvage antiretroviral therapy - Davis, Ashlyn Samantha Christal (My University, 2020)
Antiretroviral drug resistance is a major concern for HIV-1 patients failing third line regimens or salvage therapy. Currently, South African patients who fail third line antiretroviral therapy (ART) have no further antiretroviral drug options or resistance test recommendations, therefore remain on heavily compromised regimens and will likely develop AIDS and die. A phenotypic susceptibility assay that could determine which antiretroviral drugs may still be effective against HIV-1 from these patients would be a valuable tool in their successful long-term treatment success. Thus, the overall aim of this study was to establish a locally relevant in vitro phenotypic susceptibility assay to allow for the phenotypic profiling of HIV-1 from South African HIV-1 positive patients failing a third-line regimen. Viral RNA was extracted from six South African HIV-1 positive patients failing a third-line regimen, and the approximately 4.5 kb gag-pol regions were successfully RT-PCR amplified and sequenced using a newly established protocol. Nucleotide sequences were submitted to the Stanford University HIV drug resistance database to describe any known antiretroviral drug resistance mutations present, and manually aligned to look at mutations in the Gag cleavage sites and PTAP insertions. Overall, all six patients were infected with HIV-1 subtype C, with a complex mixture of known drug resistance mutations to the various ARV drug classes, in line with their current (and previous) drug regimen. Looking at the Gag cleavage sites, CA/P2 showed no changes, whereas various mutations were detected in MA/CA, P2/NC, NC/P1 and P1/P6. Intact PTAP motifs were observed in all six patient samples, and virus from two patients had an additional full or partial PTAP motif. An in vitro phenotypic inhibition assay was successfully set up using the wild type HIV-1 subtype B pNL4.3.Luc.R-E- and its performance and robustness was tested against a panel of ARV drugs. IC50 values against pNL4.3.Luc.R-E- were obtained for one protease inhibitor, six reverse transcriptase inhibitors and two integrase inhibitors. The next step was to create patient derived gag-pol pseudoviruses/expression vectors for substitution of pNL4- 3.Luc.R-.E- in these assays. Within the time constraints of the study, multiple attempts using Gibson assembly and traditional restriction/ligation cloning of gag-pol into the pNL4-3.Luc.- R.-E backbone (and a psPAX2 backbone) were unsuccessful. Overall, genotypic sequence analysis of the Gag-pol confirmed that the known HIV-1 drug resistance profiles from each of the six patients used in this study were unique, justifying future phenotypic testing, and compensatory mutations in Gag may contribute to overall resistance. Future optimization of the protocols described here to successfully create a locally relevant HIV-1 subtype C in vitro phenotypic susceptibility assay for use by patients failing third line ART is critical.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2020